Residential segregation and overweight/obesity among African-American adults: A critical review - Irma eCorral; Hope eLandrine; Marla Bianca Hall; Jukelia eBess; Kevin eMills; Jimmy eEfird (Frontiers Media S.A., 2015)
The relationship between residential segregation and overweight/obesity among African-American adults remains unclear. Elucidating that relationship is relevant to efforts to prevent and to reduce racial disparities in obesity. This article provides a critical review of the 11 empirical studies of segregation and overweight/obesity among African-American adults. Results revealed that most studies did not use a valid measure of segregation, many did not use a valid measure of overweight/obesity, and many did not control for neighborhood poverty. Only four (36% of the) studies used valid measures of both segregation and overweight/obesity and also controlled for area-poverty. Those four studies suggest that segregation contributes to overweight and obesity among African-American adults, but that conclusion cannot be drawn with any certainty in light of the considerable methodological problems in this area of research. Suggestions for improving research on this topic are provided.